EFEKTIVITAS INTERVENSI KONSELING TERHADAP WORK-LIFE BALANCE (WLB) PEGAWAI DIVISI SDM & UMUM PT X - Husain, Sayyid Daud Husain Akbar (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
The imbalance between work and personal life has become a serious challenge for many employees in modern industrial settings. This study aims to examine the effectiveness of counseling interventions in improving work-life balance among employees of the HR & General Affairs Division at PT X. Using a qualitative case study approach with a one group pretest-posttest design, two subjects (NL and LA) were selected based on their low initial work-life balance scores. The intervention consisted of three counseling sessions focusing on self-awareness, stress management, relaxation techniques, mindfulness, and light physical exercise. Results showed an increase in work-life balance scores from low to moderate and high categories, with an average N-Gain of 31.5%. Beyond quantitative improvements, qualitative data indicated positive behavioral changes, including better time management, emotional regulation, and awareness of personal limits. The counseling sessions helped employees recognize the importance of life balance and reduce maladaptive work-centered thought patterns. Overall, the findings suggest that counseling interventions effectively enhance employees’ psychological well-being and work productivity in industrial organizational contexts.